Fatores que influenciam na adesão e permanência do tratamento farmacológico e não farmacológico do paciente com diabetes mellitus tipo 2 - SOUSA, Andressa Costa de (2019)
Diabetes mellitus (DM) is defined as a group of diseases characterized by hyperglycemia due to insuline deficiency in secretion, action, or both. There are several types of DM, among them is distinguished the type 2, which corresponds to approximately 90 to 95% of the cases. The exact etiology of type 2 diabetes is not fully understood, but it is known that the hereditary factor in this type has greater importance than in type 1. As a progressive disease, DM type 2, in the majority of cases, will require medication administration, since isolated non-pharmacologic strategies are insufficient to maintain adequate glycemic control. This study aimed to: reveal the factors that influence the adherence of type 2 DM patients treatment; describe the social, demographic, economic, and epidemiological profile of patients with DM; identify the types of treatment provided and realized. This is a descriptive, transversal, quantitative study. The interviewed patients profile of in HUJBB during this research was characterized mostly as women, between 50 and 59, living in urban areas, with complete or incomplete secondary education, brown and with family income between 1-2 minimum wage. It highlights the importance of the poor knowledge level of the patients about possible complications caused by the disease, since this fact influences the adherence of treatment. It is noteworthy the poor knowledge of the patients about possible complications of the disease, since this fact influences the adherence to treatment. Therefore, it is necessary to be pro-active and be aware of the knowledge level of patients during the multidisciplinary consultation and strategizes between patients and health professionals with the objective to overcome the lack of knowledge of diabetic patients abour their disease. It was possible to conclude from this research that the variables that influence treatment adherence in diabetes are multifactorial. However the main can be classified as: characteristics of treatment - long duration, financial cost, fixed rules and undesirable effects; behavior of the patient - resistance to change the lifestyle; social factors - family support and confidence in the health professionals.